2008
DOI: 10.1007/s10567-008-0038-8
|View full text |Cite
|
Sign up to set email alerts
|

Parental Social Cognitions: Considerations in the Acceptability of and Engagement in Behavioral Parent Training

Abstract: Behavioral parent training (BPT) is a widely used, evidence-based treatment for externalizing child behaviors. However, the ability of BPT programs to be maximally effective remains limited by relatively low rates of acceptance, attendance, and adherence to treatment. Previous reviews have focused on a variety of demographic and mental health characteristics of parents and children that are predictive of poor outcomes in BPT. This paper focuses instead on consideration of parental social cognitions, and how in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
84
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 110 publications
(132 reference statements)
2
84
1
Order By: Relevance
“…However, questions remain about the link between attributional style and engagement in treatment as other studies have found no relationship between parent-referent attribution styles and treatment participation (Nordstrom, Dumas, & Gitter, 2008;Williford, Graves, Shelton, & Woods, 2009). Mah and Johnston's (2008) review suggested that addressing parent cognitions within the context of CPT programs may help to increase treatment effectiveness and that the mixed findings in the research may be attributed to timing in which these attribution interventions are implemented (pre, during, post treatment) and specific types of attributions (attributions for misbehavior, acceptability of CPT programs, efficacy in parenting) that are assessed. Parental attributions related to reasons for child misbehavior were targeted in this study to determine if a significant effect was found and to assess the magnitude of the effect.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, questions remain about the link between attributional style and engagement in treatment as other studies have found no relationship between parent-referent attribution styles and treatment participation (Nordstrom, Dumas, & Gitter, 2008;Williford, Graves, Shelton, & Woods, 2009). Mah and Johnston's (2008) review suggested that addressing parent cognitions within the context of CPT programs may help to increase treatment effectiveness and that the mixed findings in the research may be attributed to timing in which these attribution interventions are implemented (pre, during, post treatment) and specific types of attributions (attributions for misbehavior, acceptability of CPT programs, efficacy in parenting) that are assessed. Parental attributions related to reasons for child misbehavior were targeted in this study to determine if a significant effect was found and to assess the magnitude of the effect.…”
mentioning
confidence: 99%
“…Questions surrounding when these attributions should be addressed during treatment (pre, during, or post) and what attributions should be targeted (responsibility for child misbehavior, acceptability of CPT programs) also remain (Mah & Johnston, 2008), and should be considered in future research. accessed by following the link in the citation at the bottom of the page.…”
mentioning
confidence: 99%
“…Several researchers have argued that some parent characteristics, such as parental cognitions, may be more readily subject to modification than other factors, highlighting the benefits of addressing the relations of these parental cognitions to treatment acceptability (Hoza et al, 2006;Kazdin, 2000;Mah & Johnston, 2008).…”
Section: Treatment Acceptability and Parental Attributionsmentioning
confidence: 99%
“…Parental attributions have been suggested as one of these parental cognitions (Hoza, Johnston, Pillow, & Ascough, 2006;Mah & Johnston, 2008;Morrissey-Kane & Prinz, 1999). In this domain, parental attributions refer to the causal explanations parents make about their child's behaviour (Whittingham, Sofronoff, Sheffield, & Sanders, 2008.…”
Section: Treatment Acceptability and Parental Attributionsmentioning
confidence: 99%
See 1 more Smart Citation